Universal Design for Learning in Action: Exploring Strategies, Outcomes, and Challenges in Inclusive Education - Catama, Bryan V (International Journal of Rehabilitation and Special Education (IJRSE), 2025)
Despite strong global advocacy for inclusive education, a gap persists between policy and classroom practice. Universal Design for Learning (UDL) offers a proactive framework to address learner diversity, but its implementation remains uneven. This narrative review examined UDL applications in inclusive education from 2014 to 2024, focusing on instructional strategies, academic and social outcomes, and implementation challenges. A structured search of Consensus and Researcher. Life databases identified empirical studies published in English during the review period. Studies were included if they presented original data on UDL strategies, outcomes, or barriers within formal school or university settings. Eight studies met the inclusion criteria. Findings show that UDL-based instruction frequently applies multiple modes of engagement, representation, and expression. Digital platforms often support access and personalization. Reported outcomes include improved motivation, academic engagement, and social inclusion, although impact varies based on implementation quality and institutional support. Key challenges involve limited training, inadequate resources, and inconsistent understanding of UDL principles. This review affirms UDL’s potential as an equity-driven framework for inclusive education. However, its success depends on sustained investment in professional development, strong leadership, and policy alignment to enable systemic adoption.